Bariatric Surgery Past and Present - Hakan Kanat, Burhan; Kutluer, Nizamettin; Doğan, Serhat (IntechOpen, 2023)
Obesity is a disease with high comorbidity and a chronic course. It affects millions of people worldwide and has great economic costs. This book describes the history and development of bariatric surgery, from its emergence in the 10th century to today. It also discusses current techniques and future advancements involving robotics and gene therapy.